Klara and the sun - Ishiguro, Kazuo, 1954- (Alfred A. Knopf, 2021)
"From her place in the store that sells artificial friends, Klara--an artificial friend with outstanding observational qualities--watches carefully the behavior of those who come in to browse, and of those who pass in the street outside. She remains hopeful a customer will soon choose her, but when the possibility emerges that her circumstances may change forever, Klara she is warned not to invest too much in the promises of humans. In this luminous tale, Klara and the Sun, Nobel Prize winner Kazuo Ishiguro looks at our rapidly changing modern world through the eyes of an unforgettable narrator to explore a fundamental question: what does it mean to love?"--